Анализ хозяйственной деятельности предприятия: учебник / В. В. Ковалев, О. Н. Волкова - Ковалев Валерий Викторович (Проспект, 2008)
Экземпляры: ЧЗ (20151111) / Инвентарный номер: 41809 / Цена: 165.10 / Сис.шифр: 65.29 / Авт.знак: К 56 / ББК: 65.290я73